Synthesis and properties of Y2O3:Eu3+ nanoflakes for security labels application using inkjet ink with electrohydrodynamic printing technique. (23rd May 2019) - Trinh, Dung Chinh; Pham, Hieu Thi; Pham, Phuong Hau Thi; Dang, Dung My Thi; Dang, Chien Mau
Y2 O3 :Eu 3+ nanoflakes are successfully synthesised by hydrothermal method with trisodium citrate as surfactant. The doping ratio of Eu 3+ ion affects the luminescent intensity of the product. X-ray diffraction (XRD), field emission scanning electron microscopy (FE-SEM), and Raman spectroscopy are used for the characterisation of size, structure and morphology of the samples prepared at different conditions. The corresponding patterns of Y2 O3 :Eu 3+ nanoflakes can be indexed to the cubic phase of Y2 O3 (JCPDS 43-1036). The flake morphology of Y2 O3 :Eu 3+ attains 98% when the molar ratio of citrate/yttrium is 0.6. Y2 O3 :Eu 3+ nanoflakes have well-organised flake morphology with the average width around 90-100 nm and the thickness around 20 nm. The Y2 O3 :Eu 3+ nanoflakes synthesised with 5-h reaction time are flower-like nanocrystals composed of numerous contorted nanoflakes linked together by edge-to-surface. The photoluminescence results show the strongest emissivity at wavelength of 618 nm due to 5 D0 → 7 F2 transition and the sample synthesised at 5-h hydrothermal reaction time has the best luminescent intensity. The crystallinity level, luminescent intensity and size of nanoparticles are elevated under annealing process. The ink for inkjet, containing synthesised Y2 O3 :Eu 3+ nanoflakes, disperses in ethyl cellulose and other necessary solvents. The experimental security labels are printed by inkjet which uses electrohydrodynamic printing technique. The lines printed by inkjet device are solid and even, with the width at 138-170 µm in PET substrate and the smallest distance of two adjacent lines at 300 µm. The experiment security labels are nearly invisible under daylight and red under UV mercury lamps with wavelength of around 254 nm.